The Role of Instagram Accounts as a Tax Counseling Tool to Increase Tax Awareness Among MSME Actors - Tomy, Chairian; Nofitasari, Susi (Universitas Indonesia Mandiri, 2025)
There is an urgent need to raise MSMEs' tax understanding because of the significant role that taxes and MSMEs play in the Indonesian economy. Indonesia has 99.1 million Instagram users in 2024, making it the country with the second-highest number worldwide. With so many users, the purpose of this study is to determine how the Instagram platform functions as a tool for tax dissemination in order to raise MSME tax awareness. This study employs a qualitative, descriptive research methodology. The study's findings suggest that using Instagram is a significant factor in raising tax awareness. The Directorate General of Taxation's (DGT) official Instagram account makes it simpler, quicker, less expensive, and more comprehensive to target MSME actors across Indonesia with various tax-related information. In order to raise public awareness of taxes, DGT should create more creative and engaging content, upload videos more frequently and consistently, and make use of Instagram's paid advertising feature. Another option to make tax dissemination through the Instagram platform significant and influence tax awareness is to work with a tax dissemination content creator specialist.